Fiscal Decentralization and Public Subnational Financial Management in Peru - Ahmad, Ehtisham; Garcia-Escribano, Mercedes (Washington, D.C. : International Monetary Fund, 2006)
There is increasing interest in fiscal decentralization in Peru as a mechanism to generate more involved decision-making at the subnational level. This is tempered with a continuing emphasis on overall fiscal stability. However, considerable work needs to be undertaken to define more clearly expenditure responsibilities and financing mechanisms that increase local accountability. In addition, a more transparent fiscal transfer system is needed, together with clarity in expenditure management at all levels of government. The paper suggests that a substantial work agenda is needed to extend the decentralization process with greater transparency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet